2009
DOI: 10.1038/modpathol.2008.176
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutational analysis supports monoclonal origin of biphasic sarcomatoid urothelial carcinoma (carcinosarcoma) of the urinary bladder

Abstract: Sarcomatoid urothelial carcinoma of the urinary bladder is an uncommon neoplasm with biphasic morphology exhibiting both epithelial and sarcomatoid components. Whether this tumor arises from a single cancer stem cell with subsequent differentiation or represents collision of the progeny of two separate cancer stem cells is a matter of controversy. To clarify its clonal origin, we analyzed the TP53 mutation status of a series of 17 sarcomatoid urothelial carcinomas using single-strand conformation polymorphism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
4
42
0
2
Order By: Relevance
“…38 Genetic studies suggest that the epithelial and sarcomatoid elements share a common monoclonal cell origin. 39,40 The reported incidence has ranged from 0.2% to 4.3%. 41 This suggestion has been confirmed in an analysis of the Surveillance, Epidemiology and End Results (SEER) database.…”
Section: Sarcomatoid Carcinoma With/without Heterologous Elements (Camentioning
confidence: 99%
“…38 Genetic studies suggest that the epithelial and sarcomatoid elements share a common monoclonal cell origin. 39,40 The reported incidence has ranged from 0.2% to 4.3%. 41 This suggestion has been confirmed in an analysis of the Surveillance, Epidemiology and End Results (SEER) database.…”
Section: Sarcomatoid Carcinoma With/without Heterologous Elements (Camentioning
confidence: 99%
“…The primers used for TP53 sequencing have been previously described [38,39]. 50 ng tumour DNA was amplified and sequencing reactions were carried out using the DNA Sequencing Kit BigDye Terminator v 1.1 Cycle Sequencing Ready Reaction Mix (Applied Biosystems, Warrington, UK), as previously described [40].…”
Section: Tp53 Mutation Analysismentioning
confidence: 99%
“…18,20 In addition, identical TP53 mutations and concordant p53 expression patterns were detected in both the epithelial and sarcomatoid tumor components in 5 of 17 patients with CS of the urinary bladder. 17 In our case, however, TP53 sequencing of exons 5, 7 and 8 in the urothelial carcinoma and in the angiosarcoma tissue failed to detect TP53 mutations, and immunostaining for p53 was positive in a very low percentage of cells in both components.…”
Section: Discussionmentioning
confidence: 71%
“…4,16 Findings from several studies lend support to the divergence hypothesis. [17][18][19][20] For example, studies examining loss of heterozygosity in patients with CS of the bladder found identical patterns between the epithelial and sarcomatoid components of the tumors, [18][19][20] although identical patterns were more frequent in genetic alterations related to early events in bladder carcinogenesis rather than those associated with later events. 18,20 In addition, identical TP53 mutations and concordant p53 expression patterns were detected in both the epithelial and sarcomatoid tumor components in 5 of 17 patients with CS of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%